Case Report: Therapeutic Drug Monitoring of Polymyxin B During Continuous Renal Replacement Therapy in Two Pediatric Patients: Do Not Underestimate Extracorporeal Clearance - Xu, Caifang; Liu, Xiaofen; Cui, Yun; Huang, Xiaolan; Wang, Yu; Fan, Yaxin; Wu, Hailan; Li, Xin; Guo, Beining; Zhang, Jing; Zhang, Yucai (Frontiers in Pharmacology, 2022)
Background: Polymyxin B has become the last choice for patient with carbapenem-resistant bacterial infection. However, the optimal dosing of polymyxin B in critically ill children receiving continuous renal replacement therapy (CRRT) remains unclear. Case Presentation: Two cases of critically ill pediatric patients (7 years old) with acute kidney injury requiring continuous renal replacement (CRRT) received polymyxin B treatment due to carbapenem-resistant organism bloodstream infections. Therapeutic drug monitoring (TDM) of polymyxin B was carried out by liquid chromatography tandem mass spectrometry (LC-MS/MS). The average steady-state plasma concentration (Css,avg) of 2–4 mg/L was set as the target level. Initial polymyxin B dose was 1 mg/kg every 12 h, and the Css,avg at 4–5th dosing were 1.76 and 1.06 mg/L for patient 1 and patient 2, respectively. TDM-guided polymyxin B dose was escalated to 2 mg/kg every 12 h for both patients, resulting in the Css,avg of 2.60 and 1.73 mg/L, and the infection was controlled subsequently. Css,avg of polymyxin B with the same dosing regimens and infusion length were different during CRRT and after termination of CRRT for both patients (2.60 mg/L vs. 4.94 mg/L with 2 mg/kg every 12 h in 2 h infusion for patient 1; and 1.73 mg/L vs. 3.53 mg/L with 2 mg/kg every 12 h in 2 h infusion for patient 2). The estimation of drug exposure (estimated by AUCss,12h at the same dose) during CRRT and cessation of CRRT showed that 45% and 51% of polymyxin B was cleared during CRRT. Conclusion: Our study showed high clearance of polymyxin B through CRRT, and supplanted dosing of polymyxin B is necessary in pediatric patients undergoing CRRT.